2003
DOI: 10.1136/jnnp.74.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endoscopic third ventriculostomy on neuropsychological outcome in late onset idiopathic aqueduct stenosis: a prospective study

Abstract: Objective: To undertake a prospective study of the long term neuropsychological outcome in patients with late onset idiopathic aqueduct stenosis (LIAS) after endoscopic third ventriculostomy. Methods: Six patients with LIAS were evaluated pre-and postoperatively using magnetic resonance imaging (MRI) and standardised psychometric testing procedures. Endoscopic third ventriculostomy was done using standard surgical techniques. The mean long term follow up was 81.2 weeks. Results: Preoperatively, all patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Burtscher et al (7) in a prospective study evaluated 6 patients affected by late-onset aqueductal stenosis using standardized psychometric testing preoperatively and postoperatively. They found improvement of preoperative deficits (usually combined deficits of memory and frontal-executive function) in all patients (full recovery in 2, good recovery in 3, and moderate recovery in 1 (65) reviewed long-term outcomes and neurological development in children affected by obstructive hydrocephalus, treated with ETV when they were younger than 9 months.…”
Section: Intellectual Outcomementioning
confidence: 99%
“…Burtscher et al (7) in a prospective study evaluated 6 patients affected by late-onset aqueductal stenosis using standardized psychometric testing preoperatively and postoperatively. They found improvement of preoperative deficits (usually combined deficits of memory and frontal-executive function) in all patients (full recovery in 2, good recovery in 3, and moderate recovery in 1 (65) reviewed long-term outcomes and neurological development in children affected by obstructive hydrocephalus, treated with ETV when they were younger than 9 months.…”
Section: Intellectual Outcomementioning
confidence: 99%
“…ETV is a valuable modern alternative to shunt implantation (4,7,8,10,12,19,43,47). That ETV does not involve implantation of foreign material is surely a point in its favor.…”
Section: Shunt or Ventriculostomymentioning
confidence: 99%
“…Another study demonstrated that endoscopic third ventriculostomy substantially improves the neuropsychological deficit in the late onset idiopathic aqueduct stenosis. These patients achieved normal or near normal cognitive function 4) . However, there has been still no report about comparison of neurocognitive function of hydrocephalic patients whose diseases are related with different aetiologies.…”
Section: Discussionmentioning
confidence: 81%
“…So, we also agree with these authors that more studies are required to resolve the pathophysiology and management of the hydrocephalus. On the other hand Burtscher et al (2001) showed that the deficit pattern of the patients with late onset idiopathic aqueduct stenosis (LIAS) was similar to that found in other hydrocephalic disorders, but was very dissimilar to hydrocephalic dementia known as "normal pressure hydrocephalus" in older patients; and they declared that third ventriculostomy improved the neuropsychological function near to normal in five of six patients with LIAS 4) . Therefore, we think that the effectiveness of the shunt surgery and third ventriculostomy on the neurocognitive function of the hydrocephalic patients should be evaluated and also compared in future studies.…”
Section: Discussionmentioning
confidence: 94%